Professor, uma profissão professada : o homem no exercício do magistério (1975 - 2005) - Nunes, Suzana Mary de Andrade (2008)
This study is about the aspects of male teacher work configuration in the period from 1975 until 2005 in Sergipe. It is based on Education History presupposes from both Cultural History and Sociology approach. The intention of this research is to comprehend the processes of professional choice, through the mechanisms of disturbance and changes accurred in a socio-historical view; the academic training and the investments in the career of teaching in the perspective of requirements and demands of a professional qualification from the lives histories of six teachers from the secondary and high education. It is expected with this investigation a contribution to the studies of teacher profession history in Sergipe.